(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Ephedrine is a thermogenic compound extracted from the shrub plant Ephedra sinica which has enjoyed worldwide use as the active ingredient in weight loss products prior to being banned from use by the FDA in 2004 following numerous adverse effect reports including cardiac arrest. A study published by Arbo et al. in 2008 hypothesised the potential anti-oestrogenic effects of ephedrine following a series of in vivo uterotrophic assays in immature female rats. Through this study we report the validation of this hypothesis by means of comparison of in silico ligand binding affinities of the isomers of ephedrine with that of 17-β-oestradiol. Furthermore the ephedrine scaffold was used as a pharmacophore for the de novo creation of high affinity novel ligands for the oestrogen receptor on the basis that the absence of the steroidal scaffold and the use of a hitherto unutilised pharmacophoric platform would mitigate many of the adverse effects associated with 17-β-oestradiol analogs and also those of the Selective Oestrogen Receptor Modulators in contemporary use.